Fingerprint Watermarking with Tamper Detection - Jasni, Mohamad Zain; Azma, Abdullah (2006)
This paper proposes a watermarking method to embed watermark data into fingerprint images, without corrupting their features. The method does not require original fingerprint image to be able to detect tamper and thus authenticate the image. We used 256 x 256 grayscale fingerprint images in our experiment. The experimental results demonstrate that the precision of tamper detection and localization is close to 100% after level-2 detection.